Lumbar spine radiographs in iow-back pain - Elmali, Nurzat; Sarac, Kaya; Baysal, Tamer; Akif Kaygusuz, M.; Ozturk, Serhat (Annals of Medical Research, 2021)
None
Keywords: s : Low-back pain, lumbar vertebrae radiographs, correlation